Immunomodulatory effects of asiatic acid and madecassoside of centella asiatica (pegaga) on j774a.1 mouse macrophage cell line - Harun, Nurul Hikmah (2020)
Macrophage plays a vital role in innate immunity to prevent or treat the host from infection. Infection is an ailment which initiated by various pathogenic microorganisms and managed by many therapeutic synthetic drugs. However, almost available synthetic drugs presented with many adverse side effects and caused to the emergence of anti-microbial resistance among pathogenic microorganisms. Therefore, alternative agents that promote immunomodulatory activities needs to be explored. Asiatic acid (AA) and madecassoside (MA) are two main bioactive components of pentacyclic triterpenes isolated from Centella asiatica have this immunomodulatory potential based on the previous studies. However, there is no scientific data related to the effects of these individual and combination compounds on normal model of J774A.1 mouse macrophage cell line. Therefore, this in vitro study tested the hyphothesis whether both compounds are able to elicit an innate immune function of macrophages. Briefly, macrophages were cultured in five groups; untreated macrophage, macrophage-treated with lipopolysaccharides as a positive control, macrophage-treated with single AA, macrophage-treated with single MA and macrophage-treated with combination AA and MA (AA+MA) for 24 hours. The immunomodulatory effects of these compounds were determined using MTT assay, an observational method for cells morphological changes, reverse transcriptase-polymerase chain reaction (RT-PCR) and Western blot analysis. In addition, Giemsa staining was also used to assess the phagocytic activity whileenzyme-linked immunosorbent assay (ELISA) and Griess assay were used to determine the production of pro-inflammatory cytokines and nitric oxide (NO) in culture supernatants of treated macrophages, respectively. The results showed both single MA and combination treatments of AA+MA did not exert any cytotoxic effects on macrophages. Furthermore, the combination treatments of AA+MA at a dosage of (25+25) μg/mL were significantly enhanced the mRNAs and proteins expression of TLR-2 and TLR-4 receptors, phagocytosis activity, mRNAs expression and production of pro-inflammatory cytokines, production of mediators; NO secretion and inducible nitric oxide synthase (iNOS) expression as well as expression of proteins involved in the signalling pathway of inflammatory response including myeloid differentiation primary response 88 (MyD88), c-Jun N-terminal kinases 1 and 2 (JNK 1/2), extracellular signal-regulated kinases 1 (ERK 1/2) and p38 as compared to the untreated macrophages and each single compound of AA and MAtreated macrophages (50 μg/mL) (p˂0.0001). In summary, the findings suggest that the combination treatments of AA+MA are able to upsurge innate immune responses of macrophages. The findings of this study suggest that the regular consumption of these compounds as a food suplement will continuously stimulate the immune system to protect against potential infections.